COVID-19 SHOCK: THE SHORT-TERM IMPACT ON THE EUROPEAN AND AMERICAN FINANCIAL MARKETS - Nicoleta Bărbuță-Mișu; Teodor Hada; Iulia Cristina Iuga; Dorin Wainberg (Oradea Journal of Business and Economics)
The new coronavirus has very seriously shaken the behavior of global financial markets. Globally, the COVID-19 shock is considered severe, even compared to the Great Financial Crisis that took place in 2007-2008. Considering the persistence of the virus, this study is designed to investigate the short-term impact of COVID-19 upon financial markets of Europe and the United States (US) in the entire year of 2020. In the research we used daily data from the period 1st January – 31st December 2020 and linear regression. The stock markets indices selected in the sample were: European stock indices DAX30, FTSE100 and CAC40 and the American stock indices DJI and S&P500. The study’s results showed that there is a significant relationship between the number of new daily cases of COVID-19 and the considered stock market indices. But there is a much stronger correlation between oil prices and stock indices than between the number of COVID-19 new cases and stock indices. We conclude that the market has been intensely agitated at a terrible level. The American, London, French and German stock markets reacted negatively to the increase in confirmed cases of COVID-19 and to the price of oil. So, the market reaction with respect to the number of COVID-19 new daily cases is significant.